MODEL PENDAMPINGAN PASTORAL BAGI REMAJA YANG MENGALAMI BROKEN HOME GUNA MEMBANGUN CITRA DAN KONSEP DIRI YANG BENAR - Wiryohadi Wiryohadi; Periskila Sitompul; Gede Widiada (Bethel Press, 2021)
Adolescence is identical with the process of searching for personal identity in community life. This process is strongly influenced by the values instilled by his parents since childhood. However, what if the parents do not carry out that function and the child is in a broken family environment. This study aims to obtain a complete portrait of the appropriate model of pastoral counseling for adolescents who experience broken homes. The researcher used a descriptive qualitative approach to photograph this phenomenon in the community with interviews and observations as data collection techniques. The results show that the image and self-concept of adolescents who experience a broken home family leads to a bad self-image and is contrary to God's Word. However, if pastoral counseling is carried out by involving families, communities and pastors intensely, the tendency will lead to positive things.